KINERJA PELTIER SEBAGAI PEMBANGKIT LISTRIK TENAGA TERMOELEKTRIK - Uyu Wahyudin; Cecep Nana Nasuha; Asep Miftahul Anwar (Jurnal Fakultas Teknik Kuningan, 2023)
The majority of power facilities in Indonesia continue to rely on fossil fuels as their primary source of energy. Nevertheless, as a step toward the implementation of renewable energy, Peltier devices can be utilized as heat-powered electric generators. The objective of this study is to assess the performance and efficacy of Peltier devices as thermoelectric power generators. On a 20 x 30 cm aluminum plate, 10 Peltier modules of type TEC1-12706 were arranged in series for this investigation. Two distinct tests, employing solar heat energy and heat energy from a vacuum separator, were conducted. Using Peltier devices with a vacuum separator resulted in a greater output, namely 0.3818 Watt at a temperature of 60 C, than using solar heat energy, which generated 0.0223 Watt at a temperature of 37 C. The efficiency of solar-powered Peltier devices was determined to be 0.24 percent, while the efficiency of a vacuum separator was 0.62 percent. However, the efficiency of Peltier devices is still insufficient for them to serve as a primary source of electricity generation.